2016
DOI: 10.1007/978-3-319-43997-6_17
|View full text |Cite
|
Sign up to set email alerts
|

Archiving Software Surrogates on the Web for Future Reference

Abstract: Abstract. Software has long been established as an essential aspect of the scientific process in mathematics and other disciplines. However, reliably referencing software in scientific publications is still challenging for various reasons. A crucial factor is that software dynamics with temporal versions or states are difficult to capture over time. We propose to archive and reference surrogates instead, which can be found on the Web and reflect the actual software to a remarkable extent. Our study shows that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The websites corresponding to that software often nicely describe and document the tool or application. Furthermore, we found that for many purposes the archived versions can be considered surrogates of the corresponding software version that was referred to in an article [5]. In this case, the publication date is a good indicator, or at least a close estimate, of the target time for linking the publication and mentioned software.…”
Section: User Access To Web Archivesmentioning
confidence: 98%
See 1 more Smart Citation
“…The websites corresponding to that software often nicely describe and document the tool or application. Furthermore, we found that for many purposes the archived versions can be considered surrogates of the corresponding software version that was referred to in an article [5]. In this case, the publication date is a good indicator, or at least a close estimate, of the target time for linking the publication and mentioned software.…”
Section: User Access To Web Archivesmentioning
confidence: 98%
“…To facilitate the discovery of an archived resource if the URL is unknown, different approaches to search Web archives by keywords have been proposed [1,2,3,4]. Another way for users to find and access archived pages is by linking past information on the current Web to the corresponding evidence in a Web archive [5]. In contrast to accessing Web archives by closely reading pages, like users do, archived contents can also be processed at scale, enabling evolution studies and big data analysis.…”
Section: Introductionmentioning
confidence: 99%
“…[4]), on the automatic understanding of scientific publications (e.g. [5]), or on linking publications with software and archiving them [6], there has been little work on joint analytics of scientific software and publications yet (e.g. [9]).…”
Section: Introductionmentioning
confidence: 99%